Literature Review: Health Aspects and Legal Protection for Children in Scotland and Indonesia - Rita Komalasari (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
This paper for the first time presents the results of research related to Health Aspects and Legal Protection for Children. The research method presented in this paper is a literature study. Two countries, Scotland and Indonesia, were included to gain various perspectives through a literature review. The results show that the Health and Legal Protection Aspects for children are still based on the philosophical approach to the welfare and best interests of children.